(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2017)
The aim of the present research work was to evaluate the safety of reconstituted dry powder amphotericin B (AmB) inhalation via nebulizer. This study was carried out on respiratory cell lines (A549, Calu-3, NR 8383), kidney cells (293T/17), human red blood cells (RBC) and aerosol properties were determined by Andersen Cascade Impactor (ACI). AmB, a lipid derivative reconstituted dry powder was formulated by lyophilization and reconstituted into distilled water at AmB concentration at 4 mg/ml. The value of MMAD, FPF were obtained as 1.7 to 2.05 ?m and 70 to 80%, respectively. The cytotoxicity test carried out by MTT assay of lipid formulations revealed a very low toxicity on respiratory cell lines such as kidney cells, than pure AmB at concentration 1 to 8 ?g/ml of AmB. In-vitro cytotoxicity results showed less toxicity to human red blood cells (RBC) than pure AmB at concentration 1 to 8 ?g/ml of AmB. Dhaka Univ. J. Pharm. Sci. 15(2): 127-134, 2016 (December)